Nutrition and body composition of elite rhythmic gymnasts from Bulgaria - Miteva, S.; Yanev, I.; Kolimechkov, S.; Petrov, L.; Mladenov, L.; Georgieva, V.; Somlev, P. (International Journal of Sports Science & Coaching, 2020)
Rhythmic gymnastics is a sport in which special consideration is given to diet and body appearance. The purpose of this study was to assess the nutrient intake and body composition of elite rhythmic gymnasts in comparison with guidelines for female gymnasts. Twenty-one elite rhythmic gymnasts from Bulgaria were divided into three groups: First National Team, mean age 24.2; Second National Team, mean age 17.8; and Junior National Team, mean age 12.6. Body fat and muscle mass were estimated by skinfold methods, and a food frequency questionnaire was applied to assess the nutrient intake. The gymnasts showed low per cent of body fat (13.9% for the First National Team, 17.0% for the Second National Team, and 15.6% for the Junior National Team) and high per cent muscle mass (44.0, 40.5, and 37.6%, respectively). They kept their weight close to the ideal one, as recommended by the coaches, and the following equation best corresponded to the recommended ideal weight: height (cm) - 118. The energy intake was lower than the calculated energy requirements, in addition to low intake of fat and carbohydrates. The relative protein intake was 1.7 g/kg for the First National Team, 1.7 g/kg for the Second National Team, and 1.9 g/kg for Junior National Team, and the energy contribution of proteins was higher than the recommended 15%. Rhythmic gymnasts should be encouraged to maintain their ideal weight without great variance from the health-related guidelines, and coaches should consider not only the body image, but also the norms relating to body composition in women when determining ideal weight.